Adverse Events Following Immunization with EPI Vaccines among the Children of an Upazilla Health Complex in Bangladesh (Bangladesh Journal of Infectious Diseases, 2025)
Background: In Bangladesh, the Expanded Programme on Immunization (EPI) is the most successful and cost-effective public health initiative, significantly reducing morbidity and mortality in children under five, despite the inevitability of some adverse events following immunization (AEFI).Objective: The purpose of the present study was to evaluate the AEFI of EPI vaccines among the children of an Upazilla Health Complex.Methodology: This hospital-based cross-sectional study was conducted among 178 conveniently selected parents of children aged ≤18 months who received EPI vaccines within the past 3 months at the EPI corner of Nabiganj Upazila Health Complex, Habiganj, Bangladesh. From July to December 2023, a pretested face-to-face, semi-structured questionnaire was used to interview study participants at their convenience. The questionnaire was generated by the socio-demographic profile of children, the children's birth history profiles, and The AEFI status of children's EPI vaccinations during the study period.Results: The EPI vaccine had been given to all children, and all of them had suffered known adverse effects. After following vaccination, 61.2% of vaccine recipients experienced adverse effects from the BCG vaccine, 38.8% from Pentavalent, 20.8% from IPV, 5.6% from PCV, 2.8% from MR, 1.7 from OPV, and 0.6% from the measles vaccine. Fever (97.8%) and injection site abscess (16.9%) were the most frequent adverse effects. In 97.2% of instances, adverse effects occurred within 24 hours, and 89.3% of instances had adverse effects that persisted